'Universal' spray droplet adhesion model – accounting for hairy leaves. (8th August 2013) - Nairn, J J; Forster, W A; van, R M; Lutman, Peter
Summary The adhesion of a spray droplet upon initial contact with a leaf surface is extremely important to spray efficacy and is dependent on dynamic interactions between droplets (formulation, size, velocity) and leaf (micro‐topography, surface chemistry, veininess, hairiness and orientation). A 'universal' spray droplet adhesion model has previously been developed, using 50% aqueous acetone contact angles as a measure of leaf surface properties; this model satisfactorily predicts initial adhesion over a range of formulation surface tensions, droplet sizes and velocities. However, it failed to fit data from hairier leaves. This study investigates initial spray droplet adhesion on hairy leaves. Two categories of hairy leaves were identified by how the droplets penetrate the leaf hairs, Wenzel (hairy) and Cassie–Baxter (super hairy). For the Wenzel‐type, a simple constant accounted for the increased droplet shatter caused by the hairs. For the Cassie–Baxter‐type, a cushioning factor was introduced to account for the absorption of kinetic energy at impact by the hair mat. The cushioning factor was estimated by measuring the relative height of the hair mat. By including these two parameters, the new model successfully predicted the mean adhesion of non‐hairy, hairy and super‐hairy plants (R2 = 0.96). This model and the underlying principles determining hairy leaf adhesion developed in this article will help develop spray formulations effective at targeting hairy‐leaved weed and crop species.